Effect of Acupuncture on Target Tissue Distribution of Schisandra lignans. Issue 2 (June 2013) - Lu, Tu-Lin; Wu, Xiao-Yan; Song, Yu; Chen, Hao; Xu, Bin; Zhou, Yuan; Huang, Zhi-Jun; Sun, Yong; Mao, Chun-Qin
Background: Recently, the combination of acupuncture and Chinese medicine as a practical strategy to treat diseases is receiving considerable attention worldwide as they are usually found to exhibit intriguing therapeutic effectiveness. The current study aimed to study the adjunct effect of acupuncture on target tissue distribution of schisandra lignans when acupuncture is combined with Schisandra chinensis . Methods: A simple and reliable high performance liquid chromatography-electrospray tandem-mass spectrometry (HPLC-ESI-MS) method for simultaneous analysis of three bioactive lignans (schisandrin, deoxyschisandrin and schisandrin B) in rat tissues was established. Using this analytical method we evaluated whether acupuncture had a synergistic effect on the tissue distribution of schisandra lignans. Results: Tissue concentrations of the three lignans in the group receiving acupuncture were significantly higher than those in the schisandra only group, suggesting that acupuncture may potently increase tissue concentrations of schisandra lignans. The highest concentrations of the three lignans occurred in the liver compared with other tissues, and tissue concentrations in the heart, spleen, lungs and kidneys were increased by 315%, 203%, 250% and 224%, respectively. In addition, retention times of the lignans in tissues were prolonged for a relative long time. Conclusions: Our date indicate that the combined use of acupuncture and Schisandra chinensis could produce a synergistic effect which could play a beneficial role on promoting the tissue distribution of lignans. This has supported our initial hypothesis. The HPLC-MS method showed good sensitivity in quantifying the three schisandra lignans in different tissues.